Application of Deep Breathing Relaxation Therapy to Reduce Post-Operative Pain Levels of Percutaneous Nephrolithotomy (PCNL) in Patients with Kidney Stones in the Eri Soedewo Pavilion Room, Fifth Floor, Gatot Soebroto Army Hospital - Hayati, Teti (JOURNAL EDUCATIONAL OF NURSING(JEN), 2021)
Kidney stones (nephrolithiasis) are the formation of hard material in the kidneys such as stones derived from minerals and salts. Small kidney stones can move to the ureter, bladder and urethra. This causes irritation. PNCL (Percutaneous Nephro Litholapaxy) surgery is one of the endourology procedures to remove stones in the kidney tract by inserting an endoscope into the chelicera through an incision in the skin. The stones are then removed or broken into small fragments and cause wounds that cause pain. Pain is an unpleasant sensory and emotional experience accompanied by potential and actual tissue damage. One of the non-pharmacological therapeutic actions in overcoming pain is by applying deep breathing relaxation techniques. Deep breathing relaxation techniques are carried out by nurses teaching clients how to take deep breaths, slow breaths (holding inspiration to the maximum) and how to exhale slowly. From this case study, it is expected to describe nursing care for post-operative PNCL patients in the application of deep breathing relaxation techniques for post-operative PNCL pain in the Eri Soedewo Pavilion Room, V floor, Gatot Soebroto Army Hospital. The case study method used in compiling this final assignment is a descriptive case study using one patient for research. Based on the case study obtained, there was a decrease in the pain scale from a pain scale of 5 to a scale of 2 after the application of deep breathing relaxation techniques. So it can be concluded that deep breathing relaxation techniques can have an effect on reducing pain in post-operative kidney stone patients.